The UK snagging process: a benchmark for residential construction - Rotimi, FE; Tookey, J; Rotimi, J.O.B. (Research Publishing Services, 2012)
The residential construction sector is under pressure to meet an ever increasing customer expectation of quality improvement on their development projects. But not all completed residential projects turn out on a clean slate and these have become a source of concern to homeowners and approving authorities. Recent study provides evidence that a significant percentage of new homeowners call back their developers to rectify snags and latent defects. Therefore this paper is undertaken to provide a benchmark for the implementation of a snagging process similar to the UK for the residential sector in New Zealand. The methodology adopted is a meta‐study of published literature relating to snagging practice in the UK. This is compared with existing building inspection practice in New Zealand and improvement areas systematically identified. It is hoped that the study would benefit the entire construction industry by serving as improvements to quality performance in residential construction in New Zealand.
Keywords: Benchmarking; UK; New Zealand; Residential construction sector; Snagging process